Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Dietary modulation of antimicrobial peptides ( HAMP and LEAP2 ) in Chinook salmon ( O ncorhynchus tshawytscha ) fed a phytobiotic functional diet: Integrated genomic characterisation and tissue‐specific expression - Roberta Marcoli; Jane E. Symonds; Seumas P. Walker; Cesar Lopez; Mark A. Preece; Christopher Battershill; Steve Bird (Journal of Fish Biology, 2026)
Antimicrobial peptides (AMPs) are key components of the innate immune system in fish, providing rapid protection against microbial pathogens. Among these, the liver‐expressed antimicrobial peptides (LEAPs), comprising LEAP‐1 (hepcidin; HAMP) and LEAP‐2, play central roles in host defence and iron regulation. In this study, we present an integrated characterisation of the genomic organisation, tissue expression and dietary responsiveness of HAMP and LEAP2 paralogues in Chinook salmon ( Oncorhynchus tshawytscha ), and assess their modulation by a phytobiotic functional feed under commercial farming conditions. Genome mining identified three functional HAMP and three LEAP2 paralogues in Chinook salmon, all retaining conserved features typical of their respective peptide families and arising from salmonid‐specific genome duplication events. Constitutive expression analysis revealed liver‐dominant expression of HAMP, whereas LEAP2 paralogues exhibited distinct tissue‐specific profiles, with LEAP2.1 and LEAP2.2 expressed predominantly in the liver and skin, and LEAP2.3 largely restricted to gills and skin. A six‐month feeding trial using a functional diet supplemented with the phytobiotic NatControl™ resulted in marked tissue‐ and paralogue‐specific upregulation of AMP gene expression. HAMP expression was upregulated across multiple immune‐relevant tissues, including head kidney, skin, spleen, liver and gills. LEAP2 paralogues also showed clear dietary responsiveness, with LEAP2.1 and LEAP2.2 upregulated in the liver and kidney, and LEAP2.3 showing strong upregulation in gills. Despite these molecular responses, no significant differences in growth or survival were observed between diet groups. Together, these findings provide the first integrated characterisation of HAMP and LEAP2 systems in Chinook salmon, demonstrate their sensitivity to dietary immunomodulation and support their use as molecular biomarkers of functional immune priming. The results further indicate that NatControl™ acts as an effective immunostimulant, enhancing innate immune readiness without compromising growth performance under non‐challenging conditions.

Impacts of coinciding ocean acidification and warming on the fatty acid profile of the pteropod Limacina helicina within the Northeast Pacific coastal region - Clara L. Mackenzie; Chen Yin V. Walker; Matthew R. Miller; Miki Nomura; Sarah Spencer; Ian P. Forster; Chrys M. Neville; Christopher M. Pearce (Frontiers in Marine Science, 2026)
Under global climate change, co-occurrence of ocean acidification (OA) and warming poses a substantial threat to marine ecosystems. The present study focused on the Strait of Georgia within the Northeast Pacific region, where conditions of aragonite undersaturation exist year-round across the majority of the water column, with further intensification expected under OA. These conditions coincide with persistent rises in mean seasonal seawater temperatures and increased prevalence of acute stressor events, such as marine heatwaves and low-pH upwelling events. Limacina helicina , a pteropod species well-represented within the region’s zooplankton communities, is susceptible to OA and warming, with documented impacts including altered shell development, growth, and survival. To date, however, there has been minimal investigation into the effects of OA and warming on the species’ fatty acid profile under regionally-relevant conditions, thereby contributing to a lack of understanding of how impacts at lower trophic levels may relay across ecosystems. To address this knowledge gap, we examined the survival and fatty acid profile of L. helicina under future conditions via a laboratory experiment during which pteropods were exposed to singular and coinciding warming (mean summer seawater temperature + 4 °C) and OA (Ω arag < 1) conditions, with fatty acid analyses carried out via gas chromatography at 48-h and 5-d timepoints. OA conditions significantly altered fatty acid proportions at 48 h, and there was an additional interactive effect of OA and warming. Temperature significantly affected survival at 5 d, although experimental starvation conditions likely confounded this result. Additionally, fatty acid analyses of L. helicina picked from historical plankton samples collected in the region over 2014–2023 were carried out to examine time-series changes in fatty acid profiles in relation to temperature records. Results indicated no significant differences in fatty acid fractions among years, though there was suggestion of a changing proportion of myristic acid over a number of year groups. Overall, findings suggest that short-term OA conditions may result in altered fatty acid composition in pteropods, potentially leading to shifts in nutritional quality and associated impacts on trophic energy transfer.

Titanite geochemistry of Devonian oxidized I-type granodiorites in New Brunswick, Canada: Implications for exploration for porphyry Cu-Mo-Au deposits in the northern Appalachians - Fazilat Yousefi; David R. Lentz; Christopher R.M. McFarlane; James A. Walker; Kathleen G. Thorne (Lithos, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Which trees matter most? The role of private garden trees and woodland cover for 3–30-300 success in seven English cities - Eleanor S. Smith; Christopher Fleet; Arjan S. Gosal; Stuart King; Hannah Walker; Ian Willey; Catherine E. Scott (Urban Forestry & Urban Greening, 2026)

Permafrost Thaw Accelerates Old Soil Carbon Release, Outpacing New Plant Inputs During a 13‐Year Tundra Warming Experiment - Emma Lathrop; Craig See; Xanthe Walker; Grant Falvo; Zev Axler; Christopher Ebert; Stephanie Kadej; Allison Kelley; Justin Ledman; Sophie Opfergelt; Heidi Rodenhizer; Edward A. G. Schuur (Global Change Biology, 2025)
Massive stores of ancient soil organic carbon (SOC) in permafrost can decompose with Arctic warming and accelerate global climate change. Declining SOC stocks are central to the permafrost carbon feedback, but direct measures of SOC loss are extremely rare due to methodological challenges related to subsidence in the Arctic. To fully capture changing SOC dynamics during thaw, we directly measured SOC stock and bulk soil radiocarbon ( 14 C) changes, while accounting for subsidence, during 13 years of permafrost thaw in a warming experiment in Interior Alaska. We found significant declines in SOC stocks: 14% (± 6%) in ambient plots that experienced regional warming and 23% (± 5%) in snow fence warmed plots, entirely in deep, mineral soil layers. Losses were largely driven by winter soil warming but were mediated by changing soil moisture and vegetation conditions. Plots with low shrub biomass had greater SOC losses, suggesting that vegetation community composition may play an important role in SOC storage. Surface soil 14 C measurements suggest that carbon inputs were three times greater in warming plots compared to ambient plots, but that decomposition increased proportionally leading to no detectable change in surface organic layers. We observed significant SOC losses of 5.2–8.1 kg C m −2 from deeper soil layers where carbon was sequestered ~2400 to ~4500 years ago. Our findings indicate that warmer soils in the winter will accelerate SOC losses, but that increasing density of shrub species through shrub expansion could help to mitigate SOC losses in deep soils. The significant loss of SOC from deep, mineral soils observed over just 13 years of ambient and experimental permafrost thaw highlights the vulnerability of this old C pool as it enters the active global carbon cycle.

Erratum to ‘Probing the pump: Soil carbon dynamics, microbial carbon use efficiency and community composition in response to stoichiometrically-balanced compost and biochar’ [Soil Biol. Biochem. 205 (2025), 109770] - George D. Mercer; Bede S. Mickan; Deirdre B. Gleeson; Evonne Walker; Christian Krohn; Christopher H. Bühlmann; Megan H. Ryan (Soil Biology and Biochemistry, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Intranasal Dimethyl Trisulfide: Long-Term Efficacy in an Acutely Lethal Large Swine Model of Cyanide Exposure - Tara B. Hendry-Hofer; Carter Severance; Christopher J. Haberkorn; Nathan Wetmore; Walker G. West; Sharmin Sultana; Dennean S. Lippner; Melissa O. Rhoomes; Brian A. Logue; Gary A. Rockwood; Vikhyat S. Bebarta (Journal of Medical Toxicology, 2025)

A common garden comparison of the microbiome and gene expression of intertidally- and subtidally-cultured Pacific oysters (Crassostrea gigas) in relation to extreme warming events - Clara L. Mackenzie; Monique R. Raap; Colleen T. E. Kellogg; Chen Yin V. Walker; Rute B. G. Clemente-Carvalho; Timothy J. Green; Christopher M. Pearce (Aquaculture International, 2025)
In order to investigate how shellfish culture in the intertidal zone may serve as a means of conferring resilience prior to subtidal deployment for commercial grow-out, a common garden experiment was carried out with juvenile Pacific oysters. Individuals were cultured under intertidal or subtidal conditions for one year, following which intertidal animals were transplanted to the subtidal site and both treatment groups were cultured together under subtidal conditions for a period of five months. During that time, microbiome and gene expression were tracked in relation to a marine heatwave event. Multivariate analyses of samples indicated a significant effect of time on gene expression, but no significant effect of culture treatment prior to and during the heatwave. Significant differences in the expression of oxidative stress and immune response genes in post-heatwave samples in comparison to pre-heatwave and heatwave samples, and between culture treatment groups post-heatwave, were detected. Results also indicated significant differences in microbiome according to culture treatment and timepoint, with increased richness observed in intertidally-cultured oysters and over time. Similarly, while the overall composition of the oyster microbiome did not vary between culture treatments, changes were observed over time. At the end of the field trial, a laboratory-based temperature and Vibrio challenge experiment was conducted to compare genomic responses of both culture treatment groups following 24-h exposure to coinciding acute warming and pathogen stressor conditions. A significant interactive effect of temperature and culture treatment on gene expression was observed, further suggesting that stress response may be influenced by prior culture treatment.

Mineral profile of infant formula in the Las Vegas market: Compliance with label and regulations, contribution to dietary reference intakes and method comparison - Desta Woldetsadik; Douglas B. Sims; Emmanuel Herrera Huerta; Timothy Nelson; Abigael Walker; Joshua Monk; Mark C. Garner; Christopher Adcock; Amanda C. Hudson; David E.B. Fleming (Food and Chemical Toxicology, 2025)

Controlled hyperthermia by flying-foxes in the wild: understanding mammalian tolerance to hotter summer conditions - Melissa J. Walker; Justin A. Welbergen; Jessica Meade; Wayne S.J. Boardman; Terry Reardon; John M. Martin; Adam McKeown; Christopher Turbill (Journal of Thermal Biology, 2025)

Probing the pump: Soil carbon dynamics, microbial carbon use efficiency and community composition in response to stoichiometrically-balanced compost and biochar - George D. Mercer; Bede S. Mickan; Deirdre B. Gleeson; Evonne Walker; Christian Krohn; Christopher H. Bühlmann; Megan H. Ryan (Soil Biology and Biochemistry, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Estimating the density of urban trees in 1890s Leeds and Edinburgh using object detection on historical maps - Eleanor S. Smith; Christopher Fleet; Stuart King; William Mackaness; Hannah Walker; Catherine E. Scott (Computers, Environment and Urban Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Long-term management of PFAS contaminated water using constructed floating wetlands: Opportunities, limitations, and implementation considerations - John Awad; Divina Navarro; Jason Kirby; Christopher Walker; Albert Juhasz (Critical Reviews in Environmental Science and Technology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Decarbonising well-insulated buildings in a warming climate: The case of adaptive thermal comfort with geothermal space heating - Hui Ben; Christopher S. Brown; Isa Kolo; Gioia Falcone; Sara Walker (Energy and Buildings, 2024)

U-Pb and Re-Os geochronology and lithogeochemistry of granitoid rocks from the Burnthill Brook area in central New Brunswick, Canada: Implications for critical mineral exploration - Nadia Mohammadi; David R. Lentz; Kathleen G. Thorne; Jim Walker; Neil Rogers; Brian Cousens; Christopher R.M. McFarlane (Geochemistry, 2024)

Development of a nature-based solution for mitigation of Pacific oyster summer mortality: use of the intertidal zone to improve resilience to environmental stressors - Clara L. Mackenzie; Monique R. Raap; Sarah Leduc; Chen Yin V. Walker; Timothy J. Green; Eliah Kim; Emaline M. Montgomery; Sierra L. M. Gray; Amy Long; Christopher M. Pearce (Frontiers in Marine Science, 2024)
In recent years, Pacific oyster growers in British Columbia (BC), Canada have experienced devastating losses due to summer mortality syndrome. While anecdotal evidence suggests that intertidally-grown oysters may fare better during mass mortality events than deep-water counterparts, there remains a lack of research examining how different culture conditions may influence severity. To address this, we compared growth, condition, histopathology, reproductive status, and survival between intertidally- and deep-water-cultured oysters over 2 years at three oyster farms in Baynes Sound (BC). A reciprocal transplant was carried out after 1 year to test the use of the intertidal as a mechanism for promotion of physiological resilience prior to deep-water deployment. Field trial results showed significantly higher final survival in oysters transferred from the intertidal to deep water (83.5%) compared to those maintained in deep water (63.6%), but only at one farm, likely as a consequence of varying physical and/or biological characteristics associated with particular farm locations. Histopathology showed little role of disease with regards to varying survival among treatments, though higher occurrence of Viral Gametocytic Hypertrophy was observed in Year 1 oysters under deep-water (62.2%) versus intertidal (37.8%) conditions. Additionally, after 2 years, there was no significant difference in oyster size nor condition index between oysters transplanted from the intertidal to deep water and those solely cultured in deep water. A laboratory-challenge experiment determined significantly different survival curves of Year 1 intertidally- and deep-water-cultured oysters under immersion/emersion and warming conditions, with final survival of 88% and 64%, respectively, under conditions of high temperature (25°C) and immersion. Likewise, Year 2 (i.e. post-transfer) intertidally- and deep-water-cultured oysters showed significantly different survival curves under laboratory-based Vibrio challenge conditions (16°C) with final survival of 63% and 34%, respectively. Results suggest that partial culture in the intertidal at some farms may be an effective method for conferring resilience to summer mortality in Pacific oysters.

Low temperature alteration of massive sulphides below the weathering front - Louisa Stokes; Katy Evans; Christopher Kirkland; Alexander Walker (Geochimica et Cosmochimica Acta, 2024)

Examining the power supplied to Earth's dynamo by magnesium precipitation and radiogenic heat production - Alfred J. Wilson; Monica Pozzo; Christopher J. Davies; Andrew M. Walker; Dario Alfè (Physics of the Earth and Planetary Interiors, 2023)

Effect of short-term exposure to air pollution on daily cardio- and cerebrovascular hospitalisations in areas with a low level of air pollution - Md Golam Hasnain; Carlos Garcia-Esperon; Yumi Kashida Tomari; Rhonda Walker; Tarunpreet Saluja; Md Mijanur Rahman; Andrew Boyle; Christopher R. Levi; Ravi Naidu; Gabriel Filippelli; Neil J. Spratt (Environmental Science and Pollution Research, 2023)
Exposure to air pollution is associated with increased cardio- and cerebrovascular diseases. However, the evidence regarding the short-term effect of air pollution on cardio- and cerebrovascular hospitalisations in areas with relatively low air pollution levels is limited. This study aims to examine the effect of short-term exposure to different air pollutants on hospital admissions due to cardio- and cerebrovascular diseases in rural and regional Australia with low air pollution. The study was conducted in five local Government areas of Hunter New England Local Health District (HNE-LHD). Hospitalisation data from January 2018 to February 2020 (820 days) were accessed from the HNE-LHD admitted patients’ dataset. Poisson regression model was used to examine the association between the exposure (air pollutants) and outcome variables (hospitalisation due to cardio- and cerebrovascular disease). The concentrations of gaseous air pollutants, Sulphur Dioxide (SO 2 ), Nitrogen Dioxide (NO 2 ), Ozone (O 3 ), Carbon Monoxide (CO), and Ammonia (NH 3 ) were below national benchmark concentrations for every day of the study period. In single pollutant models, SO 2 and NO 2 significantly increased the daily number of cardio- and cerebrovascular hospitalisations. The highest cumulative effect for SO 2 was observed across lag 0–3 days (Incidence Rate Ratio, IRR: 1.77; 95% Confidence Interval, CI: 1.18–2.65; p -value: 0.01), and for NO 2 , it was across lag 0–2 days (IRR: 1.13; 95% CI: 1.02–1.25; p -value: 0.02). In contrast, higher O 3 was associated with decreased cardio- and cerebrovascular hospitalisations, with the largest effect observed at lag 0 (IRR: 0.94; 95% CI: 0.89–0.98; p -value: 0.02). In the multi-pollutant model, the effect of NO 2 remained significant at lag 0 and corresponded to a 21% increase in cardio- and cerebrovascular hospitalisation (95% CI: 1–44%; p -value = 0.04). Thus, the study revealed that gaseous air pollutants, specifically NO 2 , were positively related to increased cardio- and cerebrovascular hospitalisations, even at concentrations below the national standards.

Impact of drying-wetting cycles on the small strain behaviour of compacted clay - Christopher Walker; Ana Heitor; Barry G. Clarke (Transportation Geotechnics, 2023)

Global review reveals how disparate study motivations, analytical designs, and focal ions limit understanding of salinization effects on freshwater animals - Richard H. Walker; Abigail C. Belvin; Joshua B. Mouser; Amanda Pennino; Stephen Plont; Christopher D. Robinson; Lucy B. Smith; Jyoti Thapa; Carl E. Zipper; Paul L. Angermeier; Sally A. Entrekin (Science of The Total Environment, 2023)

Performance of constructed floating wetlands in a cold climate waste stabilization pond - Muhammad Arslan; Sarah Wilkinson; M. Anne Naeth; Mohamed Gamal El-Din; Zimran Khokhar; Christopher Walker; Terry Lucke (Science of The Total Environment, 2023)

Can homogeneous nucleation resolve the inner core nucleation paradox? - Alfred J. Wilson; Dario Alfè; Andrew M. Walker; Christopher J. Davies (Earth and Planetary Science Letters, 2023)

Isolation and identification of arbuscular mycorrhizal fungi from an abandoned uranium mine and their role in soil-to-plant transfer of radionuclides and metals - Jeanette Rosas-Moreno; Christopher Walker; Katie Duffy; Claudia Krüger; Manuela Krüger; Clare H. Robinson; Jon K. Pittman (Science of The Total Environment, 2023)

Estimating source-sink distributions and fluxes of reactive nitrogen and sulfur within a mixed forest canopy - Zhiyong Wu; John T. Walker; A. Christopher Oishi; Tomer Duman; Gabriel Katul; Xi Chen; Donna Schwede; Jesse Bash; John Iiames (Agricultural and Forest Meteorology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

The effects of water chemistry and lock-mediated connectivity on macroinvertebrate diversity and community structure in a canal in northern England - Jack R. Walker; Christopher Hassall (Urban Ecosystems, 2021)

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A COVID-19 Airway Management Innovation with Pragmatic Efficacy Evaluation: The Patient Particle Containment Chamber - Lauren M. Maloney; Ariel H. Yang; Rudolph A. Princi; Alexander J. Eichert; Daniella R. Hébert; Taelyn V. Kupec; Alexander E. Mertz; Roman Vasyltsiv; Thea M. Vijaya Kumar; Griffin J. Walker; Edder J. Peralta; Jason L. Hoffman; et al. (Annals of Biomedical Engineering, 2020)
The unique resource constraints, urgency, and virulence of the coronavirus disease 2019 pandemic has sparked immense innovation in the development of barrier devices to protect healthcare providers from infectious airborne particles generated by patients during airway management interventions. Of the existing devices, all have shortcomings which render them ineffective and impractical in out-of-hospital environments. Therefore, we propose a new design for such a device, along with a pragmatic evaluation of its efficacy. Must-have criteria for the device included: reduction of aerosol transmission by at least 90% as measured by pragmatic testing; construction from readily available, inexpensive materials; easy to clean; and compatibility with common EMS stretchers. The Patient Particle Containment Chamber (PPCC) consists of a standard shower liner draped over a modified octagonal PVC pipe frame and secured with binder clips. 3D printed sleeve portals were used to secure plastic sleeves to the shower liner wall. A weighted tube sealed the exterior base of the chamber with the contours of the patient’s body and stretcher. Upon testing, the PPCC contained 99% of spray-paint particles sprayed over a 90s period. Overall, the PPCC provides a compact, affordable option that can be used in both the in-hospital and out-of-hospital environments.

Stimulation of isoprene emissions and electron transport rates as key mechanisms of thermal tolerance in the tropical species Vismia guianensis - Tayana B. Rodrigues; Christopher R. Baker; Anthony P. Walker; Nate McDowell; Alistair Rogers; Niro Higuchi; Jeffrey Q. Chambers; Kolby J. Jardine (Global Change Biology, 2020)
Tropical forests absorb large amounts of atmospheric CO 2 through photosynthesis, but high surface temperatures suppress this absorption while promoting isoprene emissions. While mechanistic isoprene emission models predict a tight coupling to photosynthetic electron transport (ETR) as a function of temperature, direct field observations of this phenomenon are lacking in the tropics and are necessary to assess the impact of a warming climate on global isoprene emissions. Here we demonstrate that in the early successional species Vismia guianensis in the central Amazon, ETR rates increased with temperature in concert with isoprene emissions, even as stomatal conductance ( g s ) and net photosynthetic carbon fixation ( P n ) declined. We observed the highest temperatures of continually increasing isoprene emissions yet reported (50°C). While P n showed an optimum value of 32.6 ± 0.4°C, isoprene emissions, ETR, and the oxidation state of PSII reaction centers (q L ) increased with leaf temperature with strong linear correlations for ETR (ƿ = 0.98) and q L (ƿ = 0.99) with leaf isoprene emissions. In contrast, other photoprotective mechanisms, such as non‐photochemical quenching, were not activated at elevated temperatures. Inhibition of isoprenoid biosynthesis repressed P n at high temperatures through a mechanism that was independent of stomatal closure. While extreme warming will decrease g s and P n in tropical species, our observations support a thermal tolerance mechanism where the maintenance of high photosynthetic capacity under extreme warming is assisted by the simultaneous stimulation of ETR and metabolic pathways that consume the direct products of ETR including photorespiration and the biosynthesis of thermoprotective isoprenoids. Our results confirm that models which link isoprene emissions to the rate of ETR hold true in tropical species and provide necessary “ground‐truthing” for simulations of the large predicted increases in tropical isoprene emissions with climate warming.

Discovery of treatment for nerve agents targeting a new metabolic pathway - Trevor Glaros; Elizabeth S. Dhummakupt; Gabrielle M. Rizzo; Ethan McBride; Daniel O. Carmany; Linnzi K. M. Wright; Jeffry S. Forster; Julie A. Renner; Ruth W. Moretz; Russell Dorsey; Mark R. Marten; Walker Huso; et al. (Archives of Toxicology, 2020)
The inhibition of acetylcholinesterase is regarded as the primary toxic mechanism of action for chemical warfare agents. Recently, there have been numerous reports suggesting that metabolic processes could significantly contribute to toxicity. As such, we applied a multi-omics pipeline to generate a detailed cascade of molecular events temporally occurring in guinea pigs exposed to VX. Proteomic and metabolomic profiling resulted in the identification of several enzymes and metabolic precursors involved in glycolysis and the TCA cycle. All lines of experimental evidence indicated that there was a blockade of the TCA cycle at isocitrate dehydrogenase 2, which converts isocitrate to α -ketoglutarate. Using a primary beating cardiomyocyte cell model, we were able to determine that the supplementation of α -ketoglutarate subsequently rescued cells from the acute effects of VX poisoning. This study highlights the broad impacts that VX has and how understanding these mechanisms could result in new therapeutics such as α -ketoglutarate.

Diversity and distribution of arbuscular mycorrhizal fungi along a land use gradient in Terceira Island (Azores) - C. D. Melo; R. Pimentel; Christopher Walker; S. Rodríguez-Echeverría; H. Freitas; P. A. V. Borges (Mycological Progress, 2020)

Variation in the sex ratio of pouch young and adult hairy-nosed wombats (Lasiorhinus latifrons and Lasiorhinus krefftii) - Matt Gaughwin; Alan Horsup; Christopher Dickman; Rod Wells; Faith Walker; David Taggart (Behavioral Ecology and Sociobiology, 2020)

Using multiple natural tags provides evidence for extensive larval dispersal across space and through time in summer flounder - Jennifer A. Hoey; F. Joel Fodrie; Quentin A. Walker; Eric J. Hilton; G. Todd Kellison; Timothy E. Targett; J. Christopher Taylor; Kenneth W. Able; Malin L. Pinsky (Molecular Ecology, 2020)
Dispersal sets the fundamental scales of ecological and evolutionary dynamics and has important implications for population persistence. Patterns of marine dispersal remain poorly understood, partly because dispersal may vary through time and often homogenizes allele frequencies. However, combining multiple types of natural tags can provide more precise dispersal estimates, and biological collections can help to reconstruct dispersal patterns through time. We used single nucleotide polymorphism genotypes and otolith core microchemistry from archived collections of larval summer flounder ( Paralichthys dentatus , n = 411) captured between 1989 and 2012 at five locations along the US East coast to reconstruct dispersal patterns through time. Neither genotypes nor otolith microchemistry alone were sufficient to identify the source of larval fish. However, microchemistry identified clusters of larvae ( n = 3–33 larvae per cluster) that originated in the same location, and genetic assignment of clusters could be made with substantially more confidence. We found that most larvae probably originated near a biogeographical break (Cape Hatteras) and that larvae were transported in both directions across this break. Larval sources did not shift north through time, despite the northward shift of adult populations in recent decades. Our novel approach demonstrates that summer flounder dispersal is widespread throughout their range, on both intra‐ and intergenerational timescales, and may be a particularly important process for synchronizing population dynamics and maintaining genetic diversity during an era of rapid environmental change. Broadly, our results reveal the value of archived collections and of combining multiple natural tags to understand the magnitude and directionality of dispersal in species with extensive gene flow.

Hydrothermal Activity and Seismicity at Teahitia Seamount: Reactivation of the Society Islands Hotspot? - Christopher R. German; Joseph A. Resing; Guangyu Xu; Isobel A. Yeo; Sharon L. Walker; Colin W. Devey; James W. Moffett; Gregory A. Cutter; Olivier Hyvernaud; Dominique Reymond (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Archaeospora ecuadoriana sp. nov. from a mountainous biodiversity hotspot area in Ecuador, and transfer of Palaeospora spainiae to Archaeospora, as A. spainiae comb. nov. - Arthur Schüßler; Christopher Walker (Mycorrhiza, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Reduction in social anxiety after MDMA-assisted psychotherapy with autistic adults: a randomized, double-blind, placebo-controlled pilot study - Alicia L. Danforth; Charles S. Grob; Christopher Struble; Allison A. Feduccia; Nick Walker; Lisa Jerome; Berra Yazar-Klosinski; Amy Emerson (Psychopharmacology, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Effects of an Experimental Water-level Drawdown on Methane Emissions from a Eutrophic Reservoir - Jake J. Beaulieu; David A. Balz; M. Keith Birchfield; John A. Harrison; Christopher T. Nietch; Michelle C. Platz; William C. Squier; Sarah Waldo; John T. Walker; Karen M. White; Jade L. Young (Ecosystems, 2018)

A new genus, Planticonsortium (Mucoromycotina), and new combination (P. tenue), for the fine root endophyte, Glomus tenue (basionym Rhizophagus tenuis) - Christopher Walker; Armelle Gollotte; Dirk Redecker (Mycorrhiza, 2018)

Communities of arbuscular mycorrhizal fungi under Picconia azorica in native forests of Azores - Catarina Drumonde Melo; Sara Luna; Claudia Krüger; Christopher Walker; Duarte Mendonça; Henrique M. A. C. Fonseca; Maria Jaizme-Vega; Artur Câmara Machado (Symbiosis, 2018)

Fine root endophytes under scrutiny: a review of the literature on arbuscule-producing fungi recently suggested to belong to the Mucoromycotina - Suzanne Orchard; Rachel J. Standish; Ian A. Dickie; Michael Renton; Christopher Walker; Derrick Moot; Megan H. Ryan (Mycorrhiza, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Resolution of a disputed albendazole result in the UK Official Control System – time for more guidance? - Michael Walker; Kirstin Gray; Christopher Hopley; Christopher Mussell; Louise Clifford; Jayanie Meinerikandathevan; Leonardo Firpo; Joanna Topping; Daniel Santacruz (Food Additives & Contaminants: Part A, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Evidence of non-extractable florfenicol residues: development and validation of a confirmatory method for total florfenicol content in kidney by UPLC-MS/MS - Dermot Faulkner; Margaret Cantley; Matthew Walker; Steven Crooks; David Kennedy; Christopher Elliott (Food Additives & Contaminants: Part A, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Engaging stakeholders in nano-EHS risk governance - Jacqueline A. Isaacs; Carol Lynn Alpert; Matthew Bates; Christopher J. Bosso; Matthew J. Eckelman; Igor Linkov; William C. Walker (Environment Systems and Decisions, 2015)

Mutational escape of CD8+ T cell epitopes: implications for prevention and therapy of persistent hepatitis virus infections - Joerg Timm; Christopher M. Walker (Medical Microbiology and Immunology, 2015)

Scutellospora savannicola: redescription, epitypification, DNA barcoding and transfer to Dentiscutata - Claudia Krüger; Christopher Walker; Arthur Schüßler (Mycological Progress, 2014)

Species composition of arbuscular mycorrhizal fungi differ in semi-natural and intensively managed pastures in an isolated oceanic island (Terceira, Azores) - Catarina Drumonde Melo; Christopher Walker; Susana Rodríguez-Echeverría; Paulo A. V. Borges; Helena Freitas (Symbiosis, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

An evidence-based consensus for the classification of arbuscular mycorrhizal fungi (Glomeromycota) - Dirk Redecker; Arthur Schüßler; Herbert Stockinger; Sidney L. Stürmer; Joseph B. Morton; Christopher Walker (Mycorrhiza, 2013)

Community well-being as a critical component of urban lake ecosystem health - Christopher Walker; Jane-Louise Lampard; Anne Roiko; Neil Tindale; Aaron Wiegand; Peter Duncan (Urban Ecosystems, 2013)

Acaulospora brasiliensis comb. nov. and Acaulospora alpina (Glomeromycota) from upland Scotland: morphology, molecular phylogeny and DNA-based detection in roots - Manuela Krüger; Christopher Walker; Arthur Schüßler (Mycorrhiza, 2011)

Population structure and genetic diversity of greater sage-grouse (Centrocercus urophasianus) in fragmented landscapes at the northern edge of their range - Krista L. Bush; Christopher K. Dyte; Brendan J. Moynahan; Cameron L. Aldridge; Heather S. Sauls; Angela M. Battazzo; Brett L. Walker; Kevin E. Doherty; Jason Tack; John Carlson; Dale Eslinger; Joel Nicholson; et al. (Conservation Genetics, 2011)

Economics of Grassland Conversion to Cropland in the Prairie Pothole Region - BENJAMIN S. RASHFORD; JOHANN A. WALKER; CHRISTOPHER T. BASTIAN (Conservation Biology, 2011)
Much of the remaining grassland, particularly in North America, is privately owned, and its conversion to cultivated cropland is largely driven by economics. An understanding of why landowners convert grassland to cropland could facilitate more effective design of grassland‐conservation programs. We built an empirical model of land‐use change in the Prairie Pothole Region (north‐central United States) to estimate the probability of grassland conversion to alternative agricultural land uses, including cultivated crops. Conversion was largely driven by landscape characteristics and the economic returns of alternative uses. Our estimate of the probability of grassland conversion to cultivated crops (1.33% on average from 1979 to 1997) was higher than past estimates (0.4%). Our model also predicted that grassland‐conversion probabilities will increase if agricultural commodity prices continue to follow the trends observed from 2001 to 2006 (0.93% probability of grassland conversion to cultivated crops in 2006 to 1.5% in 2011). Thus, nearly 121 million ha (30 million acres) of grassland could be converted by 2011. Conversion probabilities, however, are spatially heterogeneous (range 0.2% to 3%), depending on characteristics of a parcel (e.g., soil quality and economic returns). Grassland parcels with relatively high‐quality land for agricultural production are more likely to be converted to cultivated crops than lower‐quality parcels and are more responsive to changes in the economic returns on alternative agricultural land uses (i.e., conversion probability increases by a larger magnitude for high‐quality parcels when economics returns to alternative uses increase). Our results suggest that grassland conservation programs could be proactively targeted toward high‐risk parcels by anticipating changes in economic returns, such as could occur if a new biofuel processing plant were to be built in an area.

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

Effects of chronic and intermittent cocaine treatment on dominance, aggression, and oxytocin levels in post-lactational rats - Josephine M. Johns; Matthew S. McMurray; Paul W. Joyner; Thomas M. Jarrett; Sarah K. Williams; Elizabeth T. Cox; Mitchell A. Black; Christopher L. Middleton; Cheryl H. Walker (Psychopharmacology, 2010)

Fifty years of change in an area of intensive agriculture: plant trait responses to habitat modification and conservation, Bedfordshire, England - Kevin J. Walker; Christopher D. Preston; Christopher R. Boon (Biodiversity and Conservation, 2009)

Contribution of mobile genetic elements to Desulfovibrio vulgaris genome plasticity - Christopher B. Walker; Sergey Stolyar; Dylan Chivian; Nicolas Pinel; Jeffrey A. Gabster; Paramvir S. Dehal; Zhili He; Zamin Koo Yang; Huei‐Che B. Yen; Jizhong Zhou; Judy D. Wall; Terry C. Hazen; et al. (Environmental Microbiology, 2009)
Summary The genome of Desulfovibrio vulgaris strain DePue, a sulfate‐reducing Deltaproteobacterium isolated from heavy metal‐impacted lake sediment, was completely sequenced and compared with the type strain D. vulgaris Hildenborough. The two genomes share a high degree of relatedness and synteny, but harbour distinct prophage and signatures of past phage encounters. In addition to a highly variable phage contribution, the genome of strain DePue contains a cluster of open‐reading frames not found in strain Hildenborough coding for the production and export of a capsule exopolysaccharide, possibly of relevance to heavy metal resistance. Comparative whole‐genome microarray analysis on four additional D. vulgaris strains established greater interstrain variation within regions associated with phage insertion and exopolysaccharide biosynthesis.

Acaulosporoid glomeromycotan spores with a germination shield from the 400-million-year-old Rhynie chert - Nora Dotzler; Christopher Walker; Michael Krings; Hagen Hass; Hans Kerp; Thomas N. Taylor; Reinhard Agerer (Mycological Progress, 2009)

The diversity of arbuscular mycorrhizas of selected Australian Fabaceae - Mark Tibbett; Megan H. Ryan; Susan J. Barker; Yinglong Chen; Matthew D. Denton; Tamara Edmonds-Tibbett; Christopher Walker (Plant Biosystems, 2008)

Cultivation of a thermophilic ammonia oxidizing archaeon synthesizing crenarchaeol - José R. De La Torre; Christopher B. Walker; Anitra E. Ingalls; Martin Könneke; David A. Stahl (Environmental Microbiology, 2008)
Summary The widespread occurrence and diversity of ammonia oxidizing Archaea suggests their contribution to the nitrogen cycle is of global significance. Their distribution appeared limited to low‐ and moderate‐temperature environments until the recent finding of a diagnostic membrane lipid, crenarchaeol, in terrestrial hot springs. We report here the cultivation of a thermophilic nitrifier (‘ Candidatus Nitrosocaldus yellowstonii’), an autotrophic crenarchaeote growing up to 74°C by aerobic ammonia oxidation. The major core lipid of this archaeon growing at 72°C is crenarchaeol, providing the first direct evidence for its synthesis by a thermophile. These findings greatly extend the upper temperature limit of nitrification and document that the capacity for ammonia oxidation is broadly distributed among the Crenarchaeota .

Diversity and infectivity of arbuscular mycorrhizal fungi in agricultural soils of the Sichuan Province of mainland China - Yuan Yuan Wang; Mauritz Vestberg; Christopher Walker; Timo Hurme; Xiaoping Zhang; Kristina Lindström (Mycorrhiza, 2008)

Opportunistic hybridization between two congeneric tropical reef fish - Stefan P. W. Walker; Christopher Ryen (Coral Reefs, 2007)

Unique vascular phenotypes following over-expression of individual VEGFA isoforms from the developing lens - Christopher A. Mitchell; Catrin S. Rutland; Michael Walker; Muneeb Nasir; Alexander J. E. Foss; Christine Stewart; Holger Gerhardt; Moritz A. Konerding; Werner Risau; Hannes C. A. Drexler (Angiogenesis, 2006)

Recovery of temperate Desulfovibrio vulgaris bacteriophage using a novel host strain - Christopher B. Walker; Sergey S. Stolyar; Nic Pinel; Huei‐Che B. Yen; Zhili He; Jizhong Zhou; Judy D. Wall; David A. Stahl (Environmental Microbiology, 2006)
Summary A novel sulfate‐reducing bacterium (strain DePue) closely related to Desulfovibrio vulgaris ssp. vulgaris strain Hildenborough was isolated from the sediment of a heavy‐metal impacted lake using established techniques. Although few physiological differences between strains DePue and Hildenborough were observed, pulse‐field gel electrophoresis (PFGE) revealed a significant genome reduction in strain DePue. Comparative whole‐genome microarray and polymerase chain reaction analyses demonstrated that the absence of genes annotated in the Hildenborough genome as phage or phage‐related contributed to the significant genome reduction in strain DePue. Two morphotypically distinct temperate bacteriophage from strain Hildenborough were recovered using strain DePue as a host for plaque isolation.

Detailed characterization of the peptide binding specificity of five common Patr class I MHC molecules - John Sidney; Shinichi Asabe; Bjoern Peters; Kelly-Anne Purton; Josan Chung; Timothy J. Pencille; Robert Purcell; Christopher M. Walker; Francis V. Chisari; Alessandro Sette (Immunogenetics, 2006)

Ecological Predictors of Extinction Risk in the Flora of Lowland England, UK - Kevin J. Walker; Christopher D. Preston (Biodiversity and Conservation, 2006)

Using Diatom Assemblages to Assess Urban Stream Conditions - Christopher E. Walker; Yangdong Pan (Hydrobiologia, 2006)

Characterization of the copper(II) binding site in the pink copper binding protein CusF by electron paramagnetic resonance spectroscopy - Andrei V. Astashkin; Arnold M. Raitsimring; F. Ann. Walker; Christopher Rensing; Megan M. McEvoy (JBIC Journal of Biological Inorganic Chemistry, 2005)

Genetic evaluation of an otter translocation program - Johanna Arrendal; Christopher W. Walker; Anna-Karin Sundqvist; Linda Hellborg; Carles Vilà (Conservation Genetics, 2004)

Class I molecules with similar peptide-binding specificities are the result of both common ancestry and convergent evolution - Alessandro Sette; John Sidney; Brian D. Livingston; John L. Dzuris; Claire Crimi; Christopher M. Walker; Scott Southwood; Edward J. Collins; Austin L. Hughes (Immunogenetics, 2003)

EXTRACELLULAR MATRIX INDUCES FORMATION OF ORGANOIDS AND CHANGES IN CELL SURFACE MORPHOLOGY IN CULTURED HUMAN BREAST CARCINOMA CELLS PMC42-LA - M. LEIGH ACKLAND; JOHN WARD; CHRISTOPHER M. ACKLAND; MARK GREAVES; MARY WALKER (In Vitro Cellular & Developmental Biology - Animal, 2003)

Extracellular matrix induces formation of organoids and changes in cell surface morphology in cultured human breast carcinoma cells PMC42-LA - Margaret Ackland; John Ward; Christopher Ackland; Mark Greaves; Mary Walker (In Vitro Cellular & Developmental Biology - Animal, 2003)

Differentiation and levels of genetic variation in northern European lynx (Lynx lynx) populations revealed by microsatellites and mitochondrial DNA analysis - Linda Hellborg; Christopher W. Walker; Eli Knispel Rueness; John E. Stacy; Ilpo Kojola; Harri Valdmann; Carles Vilà; Barbara Zimmermann; Kjetill S. Jakobsen; Hans Ellegren (Conservation Genetics, 2002)

Infestations of wild adult Atlantic salmon (Salmo salar L.) by the ectoparasitic copepod sea louse Lepeophtheirus salmonis Krøyer: prevalence, intensity and the spatial distribution of males and [2pt] females on the host fish - Christopher D. Todd; Alan M. Walker; Jane E. Hoyle; Sally J. Northcott; Andrew F. Walker; Michael G. Ritchie (Hydrobiologia, 2000)

Control of voluntary and reflexive saccades - Robin Walker; David G. Walker; Masud Husain; Christopher Kennard (Experimental Brain Research, 2000)

A major histocompatibility complex class I allele shared by two species of chimpanzee - Stewart Cooper; Erin J. Adams; R. Spencer Wells; Christopher M. Walker; P. Parham (Immunogenetics, 1998)